Why is Austria's Pension System So Much Better Than Germany's? - Florian Blank; Camille Logeay; Erik Türk; Josef Wöss; Rudolf Zwiener (Intereconomics, 2016)
The pension systems in both Germany and Austria have undergone substantial reforms, though only one of the countries appears to have had success. Average earners in Austria will receive gross pensions equivalent to 78.1% of their average earnings, whereas in Germany they will receive just 37.5%. The authors argue that Germany has been left with a system that has abandoned the goal of protecting people's standard of living.
Keywords: 330; Altersvorsorge; Rentenreform; Vergleich; Deutschland; Österreich